THE ETHNODEMOGRAPHIC SITUATION OF THE KYRGYZ IN THE SECOND HALF OF THE NINETEENTH AND EARLY TWENTIETH CENTURIES (For Piszpek and Przewalski counties) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
This article presents a comprehensive analysis of the ethnodemographic situation of the Kyrgyz population during the specified historical period. The study examines the dynamics of natural population growth, birth and mortality rates, as well as the estimation of the number of victims of the events of 1916. The research is based on archival documents, statistical data, and academic studies, which enabled a thorough analysis of demographic processes. The presented material may be useful for historians, demographers, and researchers studying ethnic history and demographic processes in Central Asia.
Keywords: Kyrgyz, population census, natural population growth, birth rate, mortality, events of 1916, statistics, archival sources